2020
DOI: 10.1097/ncq.0000000000000421
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial Comparing Outcomes of 3 Types of Peripheral Intravenous Catheters

Abstract: Welcome to the CDC website on Sharps Safety. Here you will find the Workbook for Designing, Implementing and Evaluating a Sharps Injury Prevention Program, which has been developed by CDC to help healthcare facilities prevent needlesticks and other sharps-related injuries to healthcare personnel. The Workbook is one part of a package of materials that is being made available on this website. Coming soon are posters about preventing needlesticks and an educational slide set that may be used for training healthc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 94 publications
1
10
0
Order By: Relevance
“…20 With regard to catheter type, in contrast to our findings, a randomized control trial conducted in adult patients requiring a PVC on three medical and surgical wards at the Hospital Clínico San Carlos showed a 29% reduction in the incidence of phlebitis with closed safety versus open PVCs, 29 while a second randomized trial confirmed that closed PVC systems are safer and more economical than open systems. 30 Further research is required to understand the reasons behind these disparate results. With regard to reinforced dressing, the previous study in adult patients requiring a PVC in the medical and surgical wards of a tertiary hospital located in Queensland, Australia found no significant difference in the effect of reinforced dressings and ordinary dressings on the incidence of phlebitis.…”
Section: Discussionmentioning
confidence: 99%
“…20 With regard to catheter type, in contrast to our findings, a randomized control trial conducted in adult patients requiring a PVC on three medical and surgical wards at the Hospital Clínico San Carlos showed a 29% reduction in the incidence of phlebitis with closed safety versus open PVCs, 29 while a second randomized trial confirmed that closed PVC systems are safer and more economical than open systems. 30 Further research is required to understand the reasons behind these disparate results. With regard to reinforced dressing, the previous study in adult patients requiring a PVC in the medical and surgical wards of a tertiary hospital located in Queensland, Australia found no significant difference in the effect of reinforced dressings and ordinary dressings on the incidence of phlebitis.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies supporting the evidence Reduction in insertion attempts Bausone-Gazda et al 6 (RCT) Reduction in infiltration/extravasation González López et al 8 (RCT) Increased dwell time González López et al 8 (RCT), Tamura et al, 9 Neo et al, 10 Penoyer et al, 13 Guenezan et al 16 (RCT) Reduction in risk of dislodgement Bausone-Gazda et al 6 (RCT), Galang et al 15 (RCT) Prevention of blood leakage Bausone-Gazda et al 6 (RCT), Easterlow et al, 7 González López et al, 8 Galang et al 15 (RCT) Cost reduction Bausone-Gazda et al 6 (RCT), González López et al 8 (RCT) Reduction in phlebitis rate González López et al 8 (RCT) Reduction in infection rate Easterlow et al, 7 González López et al 8…”
Section: Outcomementioning
confidence: 97%
“…McNeill et al, 5 Bausone-Gazda et al 6 (RCT), Galang et al 15 (RCT) Improved patient satisfaction/comfort Easterlow et al, 7 González López et al 8 (RCT), Galang et al 15 (RCT)…”
Section: (Rct) Improved Clinician Satisfactionmentioning
confidence: 99%
See 2 more Smart Citations